Deteksi Keberadaan Penyakit CVPD (Citrus Vein Phloem Degeneration) dengan Teknik PCR (Polymerase Chain Reaction) di Dusun Untalan Desa Jungutan Kecamatan Bebandem Kabupaten Karangasem - PUTRA, I KADEK PURNAWIRAWAN; ADIARTAYASA, WAYAN; ADNYANA, I MADE MEGA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.4, Oktober 2016, 2016)
Detection of CVPD ( Citrus Vein Phloem Degeneration ) Disease Using PCR Technique of Citrus from Untalan Sub Village, Jungutan Village, Bebandem District, Karangasem Regency This research aims to know about presentation of CVPD disease on citrus plants and detect CVPD disease using PCR technique with specific primer called 16S rDNA. This research was conducted at Laboratory of Genetics Resource and Biology Moleculer, Udayana University. Result for visual monitoring of presentation in CVPD symptom in four locations is 25%, 37%, 27%, 19%, and the average is 27%. The result for average the presentation of CVPD symptom in the shoot of citrus in each locations is 7.9%, 15.73%, 8.9%, and 7.07%. The isolation of leaves citrus DNA were appeared on 1% agarose in electrophoresis showed DNA band. The result of DNA amplified that were appeared on 1% agarose in electrophoresis showed DNA bands 1160 bp. 3 samples from 4 with specific symptom of CVPD gave positive PCR reaction. DNA Bands 1160 bp is expression by Liberobacter asiaticum, than the sample from Untalan Sub Village were detected positive for the Liberobacter asiaticum and the samples were infected by CVPD disease.
Keywords: CVPD, Untalan Sub Village, Liberobakter asiaticum, PCR